Pengaruh Penerapan Model Pembelajaran Student Facilitator And Explaining Terhadap Hasil Belajar Mata Pelajaran Ilmu Statika dan Tegangan Kelas X Teknik Gambar Bangunan SMK N 1 Padang - 1765-1781 , Yosni Juni Dola (CIVED, 2016)
This Research is based on poor student’s learning outcomes in ‘subjects Statics Science and Voltage’. In this research, writer applied Student Facilitator And Explaining. The purpose of this research was to determine whether there was effects of is influence learning model  SFE on learning outcomes in the subjects of  ‘Statics Science and Voltage’ subjectat class X Architecture Engineering SMK N 1 Padang.This research was Experimental research with Pretest-Posstets Control Group Design. Population in this research was 98 students of class X TGB. Samples that eligible for thisresearch were 2 clases of ciass  X TGB wich were class X GB-A as an experimental class and class X GB-B as the control class. Instruments used in this study were pretest and posttest in the form of an objective that amounted to 20 items that had been tested for validity, reliability, difficulty  differentiation. Data were analyzed by t-test (double average differential) on values of Gain Scores (The Difference between postets).The results showed in experimental class with an average score of posttest 86, 93, whereas in control class average score of  postets 73.93. Then, t-test obtained thitung = 3,951  ttabel = 2.000 at α = 0.05 signification. It can be concluded that the applicatin use of models pembelajan SFE significant  impact on learning outcomes  Statics Science and Voltage.  Keybords : Cooperative type SFE. Learning Outcome, Results Subjects Statics and Voltage